The Implications of Artificial Intelligence for the Future of the Workforce Markets - Pasupuleti, Mahesh Babu (i-Proclaim, 2021)
Contrary to output and employment statistics, mechanization and artificial intelligence has always been viewed as threats to job security. Modern industrial robotization with worker replacement raises unemployment, yet there is evidence of its reduction. This book shows how, despite inevitable robotization and job loss, new trades and professions will emerge, just as in the previous three revolutions, in all sectors of goods, services, and the military. However, current publications confront them with the technological trend of the twentieth century, company activity, and its effect on the future labor market. Statistically, highly qualified organizations and employees adapt quickly. Negative implications include loss of low-skilled worker competitiveness, loss of union bargaining power, increased gender pay gap, and wider gap between high-tech industrialized and undeveloped countries. It is concluded that immediate improvements are required in educational programs, labor reforms, and financial reforms. Less developed countries will continue to fall behind unless they reform their economic policies innovatively and pragmatically.